PENGEMBANGAN SISTEM INFORMASI DAN MANAJEMEN LABORATORIUM PADA PROGRAM STUDI PENDIDIKAN BIOLOGI DENGAN METODE MVC (MODEL, VIEW, CONTROLLER) - Himawan, Ahmad (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2025)
Practicum is one of the important things in the implementation of biology learning that applies concept understanding. The Biology Education study program at FKIP UNTAN has 21 practicum courses from the total courses in the study program. Some of these courses have practicum activities carried out in the laboratory. In supporting practicum activities in the laboratory, the Biology Education Study Program has a web-based Laboratory Information System (SIMLAB) that facilitates various functions such as scheduling practicum, borrowing menu, and collecting practicum reports. However, in its implementation, SIMLAB experienced several obstacles that hampered the effectiveness of practicum activities. This research was conducted to develop and improve SIMLAB so that it can function optimally as a supporting tool for laboratory management in the long term. This research uses an integrated research method between innovation in the field of technology MVC (Model, View, Controller) approach and education in the form of Research and Development (R&D) method. The data collected through the results of the R&D method needs analysis is then implemented in the form of MVC in developing SIMLAB applications. Application testing is carried out using alpha testing and beta testing to ensure the features in the application run according to their functions. The results of this study can be said to be successful in optimizing the features / menus in the application. Through this research not only produces functional application development, but also creates technological solutions that can increase the effectiveness and efficiency of laboratory management in biology education study programs. Keywords: Practicum, Web-based Application, Information System, SIMLAB